Three new species of Collembola from Sicily with first record of the genus Superodontella Stach, 1949 from Italy - Giuga, Luca; Jordana, Rafael; Baquero, Enrique (Zootaxa, 2023)
Three new species of soil Collembola from both agricultural lands (vineyards and olive orchards) and a natural habitat (beech forest) located in Sicily (Italy) are described: Superodontella eleonorae sp. nov., first record of this genus for Italy, Lepidocyrtus rapitalai sp. nov. and Pseudosinella francae sp. nov..